ALTERNATIVE APPROACH IN SDVING MESH DEPENDENCY PROBELEM IN FEM MODEL OF TUNNEL THAT EXHIBITS STRAIN SOFTENING BEHAVIOUR - Kurniawan, Fajar
One of the important aspect to be considered in underground mining activities is the stability of the tunnel, especially the behavior of the surrounding rock mass. When reaching the yield point the rock mass will exhibit three types of behavior known as post peak behaviour: perfectly elasto-plastic, strain hardening, and softening strains. The stability of a tunnel can be known through numerical modeling. In this final project, modeling is done using Rocsience Phase2 software which applies Finite Element Method (FEM). In this method, the model is divided into small elements that form a unity known as a mesh. These elements are connected by a point called nodes. In this research, FEM method is performed to produce displacement output. The problems encountered in modeling using the method is a mesh dependency. As a result, mesh of different sizes will give different displacement results. In the analytic method, the result of the displacement is only one value. Thus, this study aims to determine the best mesh in the FEM method that provides a value of displacement in accordance with the results of the analytical method. Through this research, it is known that the number of segments in the tunnel will affect the number of elements that make up the mesh. The segment that gives results according to the calculation of the analytical method is the segment 176. Furthermore, this segment is used as a reference to bring the displacement value generated by adjacent segments on the softening strain behavior using cohesion adjustment and friction angle in the residual.